FAKTOR YANG MEMPENGARUHI KAPASITAS VITAL PARU LANSIA DI KELURAHAN KARANGGENENG KECAMATAN BOYOLALI KABUPATEN BOYOLALI TAHUN 2010 - Lintang Dian Saraswati (Kesmas Indonesia, 2011)
ABSTRACT In elderly lung function decline due to reduced elasticity of the respiratory muscle fibers, decline in lung function will be more severe if the person concerned has smoking and lack of exercise. The research was to prove the association of smoking and exercise habits with lung vital capacity of elderly in Karanggeneng, Boyolali. This research was an analytical survey using cross sectional study. The populations study were elderly men aged ≥ 60 years who lived in the village of Karanggeneng.The subjects were 52 elderly taken by simple random sampling technique. Subjects underwent pulmonary function test to assess FEV1/FVC, FEV1, and FVC. The results showed that there was an association of smoking habits (p = 0.013), duaration of smoking (p = 0.001), type of cigarettes (p = 0.017), and exercise (p = 0.017) with lung vital capacity. However, there were not proven association of smoking status, frequency of smoking, type of exercise, frequency of exercise, exercise duration, and exercise habits with lung vital capacity. The conclusion was smoking habits related with the decline of lung vital capacity and exercise regularly can reduced it so it was suggested for the elderly to stop smoking and do exercise regularly. Kata Kunci : lansia, kapasitas vital paru, olahraga, merokok Kesmasindo, Volume 4(2)Juli 2011, hlm. 137-149